Half diallel analysis in indigenous genotypes of fenugreek (Trigonella foenum-graecum L.): Half diallel analysis of fenugreek - Sawargaonkar, Shrikant L; Singh, A K; Sahu, Mahendra K; Agrawal, Sarita (Journal of Spices and Aromatic Crops, 2025)
To study the nature of gene action and its components, six genotypes of fenugreek were crossed in a half diallel mating design during Rabi 2017-18, resulting in fifteen one-way F1 hybrids which were evaluated in the experimental field of the Indira Gandhi Krishi Vishwavidyalaya, All India Coordinated Research Project on Spices, College of Agriculture and Research Station (CARS), Raigarh, Chhattisgarh with two checks during rabi season, 2018–19 in a randomized complete block design with three replications. Diallel analysis of indigenous landraces of fenugreek was conducted to identify and develop elite ‘pure lines’ for subsequent use in fenugreek breeding programmes. Crosses with high SCA effects were arranged in the order of their per se performance, general combining ability of the parents of these crosses and per cent superiority over standard check RMT 305 and Hisar Sonali. Best GCA effects and high mean performance parents were observed between high × high, high × low or low × low general combiners for different traits. The best recombinants were observed for IFHyb-4, IFHyb-11, IFHyb-7, and IFHyb-9 which were best for days to 50 % flowering, primary branches, secondary branches, and seed yield respectively, which belonged to high x low combining parents, indicating non additive x additive effects and additive x additive effects. This suggests that single plant selection would be desirable in their segregating generations. High heritability coupled with low genetic advance was recorded for days to 50 % flowering, secondary branches per plant, pod length, and seed yield (q/ha) which were regulated by non-additive gene action and presence of high genotype x environment interaction.